ENT 530 Business Plan : Coatmet / Nuruh Haidah Saharrudin ... [et al.] - Saharrudin, Nuruh Haidah; Saahal, Hanisah; Rowin, Clement; Mohd Farizan, Muhammad Hilman; Manan, Misshirley (2018)
Cleo Maju is a firm that offers a product for health security and protection to motorcycle riders during their mobility on the road during raining. We would like to produce our own raincoats whereby the raincoats are knitted-with the helmets. With this, the motorcycle riders have no worries about not bring their raincoat during raining. They will protect from the rain and accident risks is reduce-as well.